MODEL SPASIAL POTENSI KERENTANAN TANAH KAWASAN PESISIR KOTA BENGKULU TERHADAP BAHAYA LIKUIFAKSI - Misliniyati, Rena; Amrina, Elita (Jurusan Teknik Sipil Universitas Bangka Belitung, 2023)
This study evaluates the susceptibility of soil liquefaction in the coastal area of Bengkulu City. The evaluation was carried out using a probability approach that includes the contribution of all seismic hazard levels that potentially trigger liquefaction, interpreted by the magnitude and maximum acceleration parameters. The soil strength parameters were collected from 26 CPT points spread along the coastal area of Bengkulu City. This evaluation implements the results of the Probabilistic Seismic Hazard Analysis (PSHA) for Bengkulu City, whereas the dominant earthquake source comes from the subduction zone of Sumatra Island. The factor of safety and the probability for each return period of liquefaction. The results of the evaluation in the form of a safety factor and probability in each return period of liquefaction are presented by a spatial model. The results show that in the return period of 475 years, the soil layer to a depth of 1 m is unsafe against liquefaction (the safety factor is less than 1) with a probability value of almost 100%. This indicates that the soil condition of the coastal area of Bengkulu City is very vulnerable to liquefaction during an earthquake. Therefore, planning the structure of houses and roads with a foundation depth of more than 1 m should be recommended to reduce potential damage due to liquefaction.